Analysis of Live Streaming Communication Strategies on Tiktok Social Media to Increase MSME Sales: A Study on Tiktok Glad2glow - Dewasanya, Amadea; Amaly, Fiqh (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The MSME sector is the main driver of economic growth in Indonesia. This is because the existence of MSMEs has provided many entrepreneurial resources and employment opportunities for the community. MSME communication strategies have begun to move towards their business activities which initially started from offline shops / door-to-door, now moving to online shops. The online shop in this study uses the TikTok application. The study on the TikTok account @Glad2Glow.indo uses the AIDA method communication strategy. The results of the study state that the AIDA model in the content of the TikTok @glad2glow.indo account, it can be concluded that the marketing communication strategy using TikTok social media as a promotional medium in this era is quite effective and able to generate lucrative profits.